2021
DOI: 10.1002/ueg2.12116
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of rotating versus single course antibiotics for small intestinal bacterial overgrowth

Abstract: Background: Small intestinal bacterial overgrowth treatment is usually based on antibiotics with no guidelines available.Objective: This study aimed to investigate the efficacy of different antibiotics to treat small intestinal bacterial overgrowth.Methods: Consecutive patients referred to our tertiary center and diagnosed with intestinal bacterial overgrowth were retrospectively included. Patients were diagnosed using a 75 g glucose breath test. Patients were treated either with a single antibiotic (quinolone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
(86 reference statements)
0
13
0
1
Order By: Relevance
“…A recently published study from 2021 compared the effectiveness of rotating antibiotics vs a single course and found it to be more effective in maintaining remission (70.8% vs 50.8%), improving quality of life and reducing bloating. This benefit may be more beneficial in those with anatomical of physiological risk factors but further research is required to elucidate these effects 50. Adverse events from recurrent antibiotic use including diarrhoea, abdominal pain and C. diff infection are fairly uncommon and occur in less than 5% of patients 45.…”
Section: Managementmentioning
confidence: 99%
“…A recently published study from 2021 compared the effectiveness of rotating antibiotics vs a single course and found it to be more effective in maintaining remission (70.8% vs 50.8%), improving quality of life and reducing bloating. This benefit may be more beneficial in those with anatomical of physiological risk factors but further research is required to elucidate these effects 50. Adverse events from recurrent antibiotic use including diarrhoea, abdominal pain and C. diff infection are fairly uncommon and occur in less than 5% of patients 45.…”
Section: Managementmentioning
confidence: 99%
“…In a retrospective study including 223 patients with SIBO, Richard et al demonstrated that, compared to patients who were treated with one type of antibiotics, those receiving rotating antibiotics (azole and quinolone) were more likely to achieve clinical remission (70% vs. 51%, respectively). Notably, remission was associated with a significant improvement in both quality of life and bloating 8 . The first author of this paper, Nicolas Richard, will receive the best paper award of UEG Journal during the UEG week.…”
Section: Figurementioning
confidence: 99%
“…Notably, remission was associated with a significant improvement in both quality of life and bloating. 8 The first author of this paper, Nicolas Richard, will receive the best paper award of UEG Journal during the UEG week.…”
mentioning
confidence: 99%
“…5 In a French monocentric and retrospective study, rotating rather than single antibiotics (quinolone or azole) were more effective for remission of SIBO using the glucose breath test, regardless of underlying disorders (including FD in up to 20%), which may be related to the use of proton pump inhibitors (PPI). 6 Indeed, only PPI were endorsed as an effective therapy for FD, with consensus for only two classes of prokinetics in gastroparesis. 1,2 In the absence of currently approved treatments in Europe, these consensus papers identify the need for novel therapeutic approaches in FD and gastroparesis.…”
mentioning
confidence: 99%
“…Another aspect of using SoMe platforms in 2021 was releasing eight episodes of the UEG Journal podcast series, giving voice to the authors, allowing for the entire route of their study process presentationfrom the initial idea to the final publication of the paper. 6,7,[20][21][22][23][24][25] The New Year is accompanied by new intentions and resolutions for further improving UEG Journal's presence in SoMe and thus continuing to provide the best access to top-notch science.…”
mentioning
confidence: 99%